The Relationship between Learning Motivation and Emotional Intelligence with Physics Learning Achievement of Public High School Students Class XI MIA in Singaraja City - Utami, Ratni Ayu; Santyasa, I Wayan; Rapi, Ni Ketut (Universitas Negeri Malang, 2018)
This research aimed to analyzing the relationship between learning motivation and physics learning achievement, emotional intelligence and physics learning achievement, and learning motivation and emotional intelligence with physics learning achievement at SMA Negeri in Singaraja city. The type of this research was ex-post facto with correlation quantitative method. The result of this research was the students’ physics learning achievement which is low and it shows that there are the positive relationship between learning motivation and emotional intelligence with physics learning achievement. Penelitian ini bertujuan untuk menganalisis hubungan motivasi belajar dan prestasi belajar fisika, kecerdasan emosional dan prestasi belajar fisika serta motivasi belajar dan kecerdasana emosional dengan prestasi belajar fisika di SMA Negeri di kota Singaraja. Jenis penelitian ini adalah ex-post facto dengan metode kuantitatif korelasional. Hasil penelitian menemukan bahwa prestasi belajar fisika siswa berada pada kategori rendah dan menunjukkan adanya hubungan positif antara motivasi belajar dan kecerdasan emosional terhadap prestasi belajar fisika